2013
DOI: 10.3233/prm-140261
|View full text |Cite
|
Sign up to set email alerts
|

Orthopedic surgery in children with intrathecal baclofen pumps

Abstract: AIMS: Children with cerebral palsy often have severe spasticity leading to deformity that requires multiple orthopedic surgeries. Intrathecal baclofen pump implantation effectively decreases severe spasticity. The objective of this study was to determine whether children who have a baclofen pump implanted at a young age have fewer orthopedic surgeries than those who have a baclofen pump implanted at later ages. METHODS: In this retrospective study of 310 children, we compared occurrence of surgery in relation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Our overall impression from our study is that the ITB therapy does not interfere with the underlying natural tendency to develop scoliosis for the most severely disabled children. Likewise, we also observed that the number of the orthopedic surgical interventions did not increase because of the ITB therapy, on contrary, both the orthopedics and the families had tendency to reconsider surgical intervention 22,23 . Because it is rational that if the patient is found relaxed compared to the prepump assessments, one may can-cel the preplanned operation for an individual, while he can identify new potential benefit and onsider orthopedic intervention 18 .…”
Section: Discussionmentioning
confidence: 59%
“…Our overall impression from our study is that the ITB therapy does not interfere with the underlying natural tendency to develop scoliosis for the most severely disabled children. Likewise, we also observed that the number of the orthopedic surgical interventions did not increase because of the ITB therapy, on contrary, both the orthopedics and the families had tendency to reconsider surgical intervention 22,23 . Because it is rational that if the patient is found relaxed compared to the prepump assessments, one may can-cel the preplanned operation for an individual, while he can identify new potential benefit and onsider orthopedic intervention 18 .…”
Section: Discussionmentioning
confidence: 59%
“…23 Similarly, a large retrospective study among a cohort of Japanese community residents demonstrated a negative relationship between BMI categories and pneumoniaassociated mortality. 27 Although the outcome of interest (mortality) in these studies differs from our research, the underlying patho- Age, median (IQR) 13 [8,15] 13 [8,14] 13 [8,15] 12 [8,14] 12 [9,14] 11 [8,14] 11 [7,14] Race possible adverse outcomes than their healthy weight counterparts.…”
Section: Discussionmentioning
confidence: 65%
“…We chose orthopedic procedures because a substantial number of children with neurologic disorders require orthopedic surgical care. [14][15][16] Moreover, studying patients undergoing orthopedic surgery would also be a way to better individualize the specific effects of the neurologic and weight comorbidities on the risk of postoperative pneumonia on the contrary of visceral surgery which has additional and possibly confounding postoperative effects on respiratory mechanics. We hypothesized that obesity in children increases the magnitude of the association between neurologic disorders and postoperative pneumonia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, ITBP did not change the osteotomy rates, which is in concordance with our results. Gooch et al 23 show that there is no significant impact of pump placement on overall orthopedic surgery frequency in 310 children with ITBP. Silva et al 24 show in their comparative study of SDR to ITBP, that in the ITBP group, 32% of hips had reconstruction procedures after ITBP.…”
Section: Discussionmentioning
confidence: 99%